Does Influencer Marketing Really Improve Sustainable Brand Awareness and Sales? - Nadia Ferina; Gede Sri; Luh Putu (Politeknik Negeri Bengkalis, 2021)
The disruption era has pushed all business activities to move to digital. The emergence of these digital activities also made many brands try to maintain their existence by increasing digital marketing activities, one of which is influencer marketing. The use of this influencer technique is on the rise, but it is also reaping various controversies about the result of its application because not all business fields experience the optimal result of increasing brand awareness and sales. The purpose of the study is to determine whether influencer marketing can improve sustainable brand awareness and sales, especially for start-up businesses.This research was conducted in Denpasar City with a phenomenological qualitative method to find out what the informants thought about the influencer marketing phenomenon to improve sustainable brand awareness and sales. Resource persons were interviewed in-depth. The data validity method is source triangulation. The results of the study indicate that influencer marketing affects the improvement of brand awareness temporally. Brands must be adaptive to apply other strategies and take advantage of the momentum to achieve optimal sales. The challenges that exist can be minimized by brands related to actively selecting influencers and adapting to other digital marketing methods, as well as conducting good communication before and after collaboration. Influencer marketing is the right marketing technique in the disruption era but must be accompanied by other marketing strategies to support maximum results.